Pengaruh Metode Pembelajaran Demonstrasi dan Eksperimen terhadap Hasil Belajar Fiqih - Adawiyah, Rabiatul; Hakim, Samsul; Sudrajat, Husaen (Journal of Teaching and Elementary Education, 2025)
The aim of this research is to increase student learning activities in the Fiqh Subject Class II MI NW Gelogor for the 2022/2023 Academic Year by applying Demonstration and Experimental Methods. This research uses a quantitative approach with a Quasi Experimental Design type of research. The research setting or location is MI NW Gelogor. Data collection techniques use observation, test and documentation methods. Observation is used to observe teaching and learning activities. Tests are used to obtain data on student learning outcomes. Meanwhile, documentation is used to obtain data regarding the profile of MI NW Gelogor, facilities and infrastructure, and student data. This research focuses on comparing learning outcomes before and after treatment (pre or post test) with the help of the SPSS 14.0 Windows application. The results of the research show that the results of the one simple t-test obtained a statistical t value (demonstration) of 9.239 > 2.131 (t table) and a p value of 0.000 < 0.050 and a statistical t value (experiment) of 17.486 > 2.131 (t table) and the p value of 0.000 < 0.050. So Ho is rejected and Ha is accepted, which means that the Demonstration and Experimental Learning Method has a positive and significant influence on the Fiqh Learning Results of Class II MI NW Gelogor Students for the 2022/2023 Academic Year